The Educational Methods According to Muhammad bin Syakir Al-Syarif in the Book Nahwa Tarbiyah Islamiyyah Rasyidah min al-Tufulah hatta al-Bulugh - Muhammad Habibi Azimi; Junaidi Arsyad; Azizah Hanum OK (UMSU, 2026)
This research analyzes the educational framework developed by Muhammad bin Syakir al-Syarif, which offers a phased model of education beginning from pre-puberty, continuing through puberty, and reaching adulthood, as a response to the weakening internalization of values in modern Islamic education. The purpose of this research is to explain the structure of his educational thought, the stages of child development, and the educational methods formulated in accordance with psychological characteristics and the principles of Islamic law. This study employs a qualitative approach through a literature review of the primary works of the author and relevant supporting references. The findings reveal that the pre-tamyiz stage emphasizes role modeling and habituation, the tamyiz stage requires dialogue and direct experience, while the baligh stage represents the phase of taklif that demands a rational and responsible educational approach through methods such as at-ta‘lim, mau‘izhah, amar ma‘ruf nahi munkar, parables, exploration, and rihlah. This study concludes that Syakir’s educational model remains relevant in addressing the dominance of cognitive-oriented approaches in contemporary Islamic education and may serve as a foundation for developing a more integrated Islamic educational curriculum.